Anthropogenic impacts on mass change in North China. Issue 15 (12th August 2013) - Tang, Qiuhong; Zhang, Xuejun; Tang, Yin
Abstract : [1] The gravity fields from the Gravity Recovery and Climate Experiment (GRACE) satellite have been used to estimate groundwater depletion in many parts of the world. Groundwater depletion assessment in North China, however, is affected by large anthropogenic disturbance on mass variation. Using the water survey data and coal flow statistics, we show that the mass variations in North China during 2003–2011 were largely affected by reservoir regulation, water diversion, and coal transport. According to our estimates, the mass loss rate of groundwater depletion (−14 to −8.4 mm yr −1 ) was largely offset by the mass gains caused by reservoir regulation (1.3 mm yr −1 ), water diversion (4.4 mm yr −1 ), and coal transport (1.9 mm yr −1 ) in the North China Plain. We note that anthropogenic impacts on mass change must be taken into account when using the GRACE data to estimate groundwater change in the area intensively altered by human activities. Key Points: Mass variations in North China were largely affected by human activities Anthropogenic mass redistribution could be comparable to groundwater depletion GRACE is capable to assess the exploitation of natural resources in North China